Integrated reporting in UK higher education institutions. Issue 5 (4th November 2019) - Hassan, Abeer; Adhikariparajuli, Mahalaximi; Fletcher, Mary; Elamer, Ahmed
Abstract : Purpose: This paper aims to examine trends in the content of reporting within 135 UK higher education institutions (HEIs). It explores the extent to which integrated reporting (IR) content elements, reflecting integrated thinking, are disclosed voluntarily and whether HEI-specific features influence the resulting disclosures. Design/methodology/approach: Existing IR guidelines given by the International Integrated Reporting Council (IIRC) and the adoption of content analysis have provided the opportunity to examine the trend and extent of IR content elements associated in HEI corporate reports. The evidence was obtained from 405 UK HEI annual reports covering the period 2014-2016. Findings: The results indicate a significant increase in the number of IR content elements embedded in HEI annual reports. The HEI-specific characteristics examined, such as the establishment of HEI (before or after 1992), adoption of IR framework and size of HEI, are all significantly and positively associated with IR content elements disclosure. This paper argues that institutional theory, isomorphism and isopraxism are relevant for explaining the changes in the contents of HEI annual reports. The findings also suggest that universities are beginning to adopt an integrated thinking approach to the reporting of their activities. Research limitations/implications: The study is based on IR content elements only and could be extended to include the fundamental concepts and basic principles of the IR framework. There are other factors that have a potentially crucial influence on HEI core activities (such as teaching and learning research and internationalisation) which have been omitted from this study. Practical implications: The findings will allow policymakers to evaluate the extent to which integrated thinking is taking place and influencing the UK HEI sector in the selection and presentation of information. A further implication of the findings is that an appropriate a sector-wide enforcement and compliance body, for instance, the British Universities Finance Directors Group (BUFDG), may consider developing voluntary IR guidance in a clear, consistent, concise and comparable format. Also, it may pursue regulatory support for this guidance. In doing so, it may monitor the compliance and disclosure levels of appropriate IR requirements. Within such a framework, IR could be used to assist HEIs to make more sustainable choices and allow stakeholders to better understand aspects of HEI performance. Social implications: The research has implications for society within and beyond the unique UK HEI sector. Universities are places of advanced thinking and can lead the way for other sectors by demonstrating the potential of integrated thinking to create a cohesive wide-ranging discourse and create engagement among stakeholder groups. Specifically, IR builds on the strong points of accounting, for instance, robust quantitative evidence collecting, relevance, reliability, materiality, comparability and assurability, to explain the sustainability discourse into a "language" logical to HEIs organisational decision makers. Consequently, IR may generate better visibility and knowledge of the financial values of exploiting capitals (financial, intellectual, human, manufactured, social and natural) and offer a multifaceted approach to reassess HEIs organizational performance in various sectors that support the growth of integrated thinking. Originality/value: This is the first known study to explore HEI characteristics and link them with the level of voluntary IR content elements disclosed in UK HEIs.